PELAKSANAAN SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN (SKMHT) DI KOTA PEKALONGAN - Dian Cahyo Wibowo; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The Power of Attorney Charging the Guarantee Right (SKMHT) in Article 15 of Law Number 4 Year 1996 concerning Land and Property Rights related to Land (UUHT) is stipulated as a condition to be immediately followed up by the making of Certificate of Granting of Mortgage Right APHT).This study uses descriptive analytical properties with aspects of the Empirical Juridical approach and field research (observation) only as supporting data. The location of this study was conducted in Pekalongan City. The population of this study amounted to 50 (fifty) SKMHT made by 4 people Notary / PPAT respondents in May - November 2014. Of the entire population are all sampled.To collect primary data / main data is done by using field research using interview technique, whereas to informant is done by giving questionnaire and interviewing them related to SKMHT implementation in crediting by creditors. To obtain secondary data / additional data is done literature on books, laws, and important documents related to this research. The data obtained were analyzed and then grouped the data according to their qualification, then described with qualitative analysis approach.The result of this thesis research shows the process of Implementation of SKMHT in credit scheme made by Notary / PPAT has been in accordance with the regulation. In the process of using SKMHT in this credit agreement is made with the stage that is before and at the time after the credit agreement agreement and the second stage merupkan SKMHT installation to the land office. The inhibiting factors in the use of SKMHT arise during the binding process into APHT and APHT registration stages. The inhibiting factors in the implementation process of SKMHT into APHT form are costly and short term. In overcoming these obstacles, efforts are made by renewing SKMHT which has expired in accordance with legislation and follow up SKMHT become APHT.Keywords: Power of Attorney Charges Deposit Rights